Grain alignment modulation and observed electrical transport properties of Ca3Co4O9 ceramics - F.P. Zhang; J.L. Shi; J.W. Zhang; X.Y. Yang; J.X. Zhang (Results in Physics, 2019)
The polycrystalline Ca3Co4O9 oxide powders were synthesized by citrate acid sol-gel method, and the Ca3Co4O9 oxide ceramics with diverse grain alignments were prepared by sintering the pressed pellet bulks through controlling the procedures, respectively. The phase compositions, grain alignments, bulk microstructures, textures as well as the electrical transport properties were investigated by means of X-ray diffraction pattern XRD, scanning electron microscopy SEM, transmission electron microscopy TEM and electrical constant measurements apparatus. The results showed that the obtained Ca3Co4O9 ceramics with uniformly single phases and diverse grain alignments can be fabricated by modulating the preparing parameters; moreover, the grain alignment can be enhanced by applying the pressure of the sintering procedure. The Ca3Co4O9 ceramics with uniformly single phase and strongest grain alignment could be fabricated with formation pressure of 500 MPa and sintering pressure of 30 MPa. The sintering pressure is a key factor enhancing the grain alignment for this type of ceramics. The ceramic sample with highest grain alignment was found to have the highest electrical properties, which showed the maximum power factor value of 3.83 μW cm−1 K−2 at 700 °C. Keywords: Ca3Co4O9 ceramics, Preparation, Grain alignments, Electrical transport properties